Effects of ingesting JavaFit Energy Extreme functional coffee on aerobic and anaerobic fitness markers in recreationally-active coffee consumers - Kreider Richard B; Wilborn Colin D; Wismann Jennifer A; Taylor Lemuel W; Roberts Michael D; Willoughby Darryn S (Taylor & Francis Group, 2007)
Abstract The purpose of this study was to examine the effects of ingesting JavaFit™ Energy Extreme (JEE) on aerobic and anaerobic performance measures in recreationally-active male and female coffee drinkers. Five male (27.6 ± 4.2 yrs, 93.2 ± 11.7 kg, 181.6 ± 6.9 cm) and five female (29 ± 4.6 yrs, 61.5 ± 9.2 kg, 167.6 ± 6.9 cm) regular coffee drinkers (i.e., 223.9 ± 62.7 mg·d-1 of caffeine) participated in this study. In a cross-over, randomized design, participants performed a baseline (BASELINE) graded treadmill test (GXT) for peak VO2 assessment and a Wingate test for peak power. Approximately 3-4 d following BASELINE testing, participants returned to the lab for the first trial and ingested 354 ml of either JEE or decaffeinated coffee (DECAF), after which they performed a GXT and Wingate test. Criterion measures during the GXT included an assessment of peakVO2 at maximal exercise, as well as VO2 at 3 minutes and 10 minutes post-exercise. Additionally, time-to-exhaustion (TTE), maximal RPE, mean heart rate (HR), mean systolic pressure (SBP), and mean diastolic blood pressure (DBP) were measured during each condition. Criterion measures for the Wingate included mean HR, SBP, DBP, peak power, and time to peak power (TTP). Participants then returned to the lab approximately one week later to perform the second trial under the same conditions as the first, except consuming the remaining coffee. Data were analyzed using a one way ANOVA (p < 0.05). Our results indicate that JEE significantly increased VO2 at 3 minutes post-exercise when compared to BASELINE (p = 0.04) and DECAF (p = 0.02) values, which may be beneficial in enhancing post-exercise fat metabolism.